THE SOCIOLINGUISTIC NATURE OF THE REPRESENTATION OF FEMALE DOMINANCE (Scientific journal of the Fergana State University, 2025)
Since the day people first opened their eyes to the world, the biological differences between them have the ability to create new awareness in the later parts of their lives. Men and women are not welcomed and accepted the same by society, and this is reflected in their psychology. That's why the psychology of men and women begins to show itself differently. Because even the business world is different for them. Men go to war, women look after children at home. This provides the basis for their sociolinguistic awareness. Language, which is used in all periods of our lives and is the main method of communication, is one of the most affected by this. The fact that women use softness, euphemisms, praise and curse expressions and idiomatic combinations more than men is also evident in the prose works of female writers. Men, on the other hand, do not apologize, take a rigid stance, and use or are forced to use excuses when they encounter an impossible situation. Women, on the other hand, have the nature of apologizing even when they haven't done anything. Because society expects this from them, but they are surprised when they hear such statements from men.